Alkaline system urea oxidation catalyst and preparation method thereof
By doping bimetallic (tungsten and cobalt) into the nickel selenide catalyst under an alkaline system, the electronic structure of the catalyst is regulated, and the carbon cloth-supported W,Co-NiSe2/CC catalyst is prepared, which solves the problem of insufficient catalytic performance of nickel selenide catalyst alone, and achieves efficient catalytic and stability of the urea oxidation reaction.
Patent Information
- Application Number
- CN202510044583.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-12
- Publication Date
- 2025-04-11
AI Technical Summary
In the prior art, the catalytic performance of the urea oxidation reaction (UOR) catalyst fails to meet the needs, especially in alkaline systems, the catalytic performance of the nickel selenide catalyst alone is insufficient for UOR.
By doping bimetallic (tungsten and cobalt) in the nickel selenide catalyst, the electronic structure of the catalyst is regulated, and a carbon cloth-supported nickel selenide-based composite catalyst W, Co-NiSe2/CC is prepared. The catalyst is prepared by a two-step hydrothermal method, first preparing a carbon cloth supported catalyst precursor, then undergoing a selenization hydrothermal reaction and high-temperature calcination to form a composite catalyst.
This catalyst not only provides more active sites for UOR, but is conducive to the diffusion of electrolytes, has excellent electrochemical reaction activity, can replace traditional precious metal catalysts, and significantly improves the catalytic activity and stability of urea electrocatalytic oxidation reaction.
Smart Images

Figure CN119812369A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrochemical catalytic oxidation and relates to a fuel cell anode catalyst, in particular to a direct urea fuel cell anode catalyst in an alkaline system and a preparation method thereof. Background Art
[0002] The continuous use of fossil fuels has led to increasingly serious environmental pollution, and there is an urgent need to find a green and pollution-free clean energy. Hydrogen energy has the characteristics of high energy density and cleanliness, and is considered to be an ideal substitute for fossil fuels.
[0003] Hydrogen production by water electrolysis is currently the most advanced hydrogen production technology, but there are still technical bottlenecks. The water electrolysis reaction includes the anode oxygen evolution reaction (OER) and the cathode hydrogen evolution reaction (HER). The high theoretical potential of OER (1.23V (vs RHE)) leads to a high economic cost of water electrolysis.
[0004] Studies have shown that using thermodynamically advantageous oxidation reactions to replace OER is an effective strategy to reduce the cost of water electrolysis. For example, urea oxidation reaction (UOR), methanol oxidation reaction (MOR), hydrazine hydrate oxidation reaction (HzOR, etc. Among them, UOR has attracted more and more attention from researchers. Its lower theoretical potential (0.37V (vs RHE)) makes it the best choice to replace OER. UOR can also be used to treat urea-rich wastewater, which is beneficial to environmental remediation.
[0005] The reaction process of urea electrocatalytic oxidation in alkaline medium is shown as follows:
[0006] Anode: CO ( NH 2)2 + 6 OH - →N 2 ↑ + 5 H 2 O+CO 2↑ + 6 e - (1)
[0007] Cathode: 6 H 2 O+ 6 e - → 3 H 2↑ + 6 OH - (2)
[0008] Overall: CO( NH 2)2 + 6 OH - →N 2 ↑ + 3 H 2↑ +CO 2↑ (3)
[0009] As can be seen from the above formula, UOR is a six-electron transfer reaction, and the low reaction kinetics hinders the practical application of UOR. Therefore, efficient catalysts are needed to promote urea oxidation.
[0010] As early as in the study by Botte et al., it was first confirmed that under alkaline conditions, the catalytic ability of transition metal nickel for UOR is superior to that of various precious metals. Following this discovery, the research on nickel-related electrocatalysts has achieved great success.
[0011] Subsequent studies have shown that nickel-based phosphides, sulfides, nitrides, selenides, etc. are considered promising UOR catalysts due to their lower cost. Among them, nickel-based selenides have larger atomic radius and smaller ionization energy than oxides and sulfides of the same metal, which contributes to faster electron transfer.
[0012] However, the catalytic performance of nickel selenide catalyst alone for UOR still fails to meet the requirements and needs to be modified. Doping, as a method that can effectively regulate the electronic structure, is widely used in catalyst modification. Summary of the invention
[0013] The purpose of the present invention is to provide an alkaline system urea oxidation catalyst and a preparation method thereof, and to further improve the catalytic activity of the nickel selenide catalyst by doping a bimetal into the nickel selenide catalyst to regulate the electronic structure of the catalyst.
[0014] Specifically, the present invention adopts the following method to prepare the alkaline system urea oxidation catalyst:
[0015] Firstly, nickel salt, tungstate and cobalt salt are dissolved in water, carbon cloth is added, and a carbon cloth-supported catalyst precursor is prepared by hydrothermal reaction at 120-140°C;
[0016] Secondly, the carbon cloth-supported catalyst precursor is placed in a liquid containing Se 2- In an aqueous solution, a selenization hydrothermal reaction is carried out at 170-190°C;
[0017] Finally, the selenization hydrothermal reaction product is calcined at a high temperature of 350-450° C. in an inert environment to prepare a carbon cloth-supported tungsten- and cobalt-doped nickel-selenide-based composite catalyst W,Co-NiSe2 / CC.
[0018] The nickel salt may be any conventional water-soluble inorganic or organic nickel salt, including but not limited to any one of nickel sulfate, nickel nitrate, nickel chloride or nickel acetate.
[0019] Furthermore, the present invention preferably uses nickel nitrate.
[0020] The tungstate can be any conventional water-soluble inorganic or organic tungstate, including but not limited to any one of sodium tungstate, calcium tungstate or ammonium tungstate.
[0021] Furthermore, the present invention preferably uses sodium tungstate.
[0022] The cobalt salt may be any conventional water-soluble inorganic or organic cobalt salt, including but not limited to any one of cobalt nitrate, cobalt chloride or cobalt sulfate.
[0023] Furthermore, the present invention preferably uses cobalt nitrate.
[0024] Furthermore, the molar ratio of the nickel salt, tungstate and cobalt salt is preferably 1:(1-2):(1-2).
[0025] More specifically, the reaction time for preparing the carbon cloth-supported catalyst precursor by hydrothermal reaction in the present invention is preferably 5 to 7 hours.
[0026] Wherein, the Se 2- The aqueous solution is obtained by reducing selenium powder with a reducing agent. The reducing agent is any reducing agent that can react with selenium powder, including but not limited to any one of hydrazine hydrate, sodium borohydride or lithium aluminum hydride.
[0027] Furthermore, the present invention preferably uses sodium borohydride as a reducing agent to reduce selenium powder in an alkaline aqueous solution to obtain the Se-containing 2- of aqueous solution.
[0028] Furthermore, the molar amount of the selenium powder is preferably 1.1 to 1.3 times the molar amount of the nickel salt.
[0029] More specifically, the time of the selenization hydrothermal reaction of the present invention is preferably 5 to 7 hours.
[0030] Wherein, the high-temperature calcination time of the selenization hydrothermal reaction product of the present invention is not less than 2 hours.
[0031] Furthermore, the present invention preferably performs high-temperature calcination by heating the selenization hydrothermal reaction product to a calcination temperature of 350 to 450° C. at a rate of 2 to 5° C. / min under an inert atmosphere.
[0032] The present invention adopts a two-step hydrothermal method. First, a carbon cloth-supported catalyst precursor WCoNi-pre / CC is prepared by hydrothermal reaction of nickel salt, cobalt salt and tungstate, and then a selenization hydrothermal reaction is performed again to obtain a bimetallic doped W,Co-NiSe2 / CC catalyst. This catalyst can not only provide more active sites for UOR, but also facilitate electrolyte diffusion and has excellent electrochemical reaction activity. It can replace traditional precious metal catalysts in the electrocatalytic oxidation reaction of urea.
[0033] Based on the above preparation method, the present invention obtains an alkaline system urea oxidation catalyst, wherein the catalyst uses NiSe2 as an active component, is doped with W and Co bimetallics, and is directly loaded on a carbon cloth.
[0034] The alkaline system urea oxidation catalyst of the present invention can be directly used as an anode material of a urea fuel cell and applied to a UOR reaction.
[0035] Due to the doping of W and Co diatoms, the electronic structure of the nickel selenide catalyst is changed, the conductivity of the catalyst of the present invention is improved, the charge transfer in the catalytic process is promoted, thereby increasing the reaction rate, and further improving the catalytic activity of the W, Co-NiSe2 / CC composite catalyst prepared by the present invention.
[0036] Furthermore, the W, Co-NiSe2 / CC composite catalyst prepared by the present invention is directly used as a working electrode, which avoids the disadvantage that the powder material will fall off, and makes the working electrode have better conductivity and stability.
[0037] Cyclic voltammetry was used to evaluate the activity of the W,Co-NiSe2 / CC composite catalyst prepared by the present invention for the electrocatalytic oxidation reaction of urea. In a 1.0 M KOH + 0.33 M Urea electrolyte, the peak current density at a voltage of 1.724 V at a scan rate of 50 mV / s can reach 363.24 mA cm -2 , has a significant catalytic effect on urea oxidation. At the same time, at a voltage of 1.424V, after 100h of chronoamperometry test, the current density retention rate was 81.6%, and the catalyst maintained good conductivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 It is the X-ray diffraction pattern of the catalyst prepared in Example 1 and Comparative Examples 1-3.
[0039] Figure 2 It is the CV curve of the catalysts prepared in Example 1 and Comparative Examples 1 to 3 in 1.0 M KOH solution.
[0040] Figure 3It is the CV curve of the catalysts prepared in Example 1 and Comparative Examples 1-3 in 1.0M KOH+0.33M Urea solution.
[0041] Figure 4 The catalysts prepared in Example 1 and Comparative Examples 1 to 3 were -2 The corresponding voltage.
[0042] Figure 5 This is a 100h chronoamperometry IT test graph of the catalyst prepared in Example 1. Implementation
[0043] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples. The following examples are only used to more clearly illustrate the technical solution of the present invention so that those skilled in the art can well understand and utilize the present invention, rather than limiting the scope of protection of the present invention.
[0044] The production processes, experimental methods or detection methods involved in the embodiments of the present invention, unless otherwise specified, are all conventional methods in the prior art, and their names and / or abbreviations are all conventional names in the field, and are very clear and unambiguous in the relevant application fields. Technical personnel in the field can understand the conventional process steps based on the names and apply the corresponding equipment, and implement them according to conventional conditions or the conditions recommended by the manufacturer.
[0045] The various instruments, equipment, raw materials or reagents used in the embodiments of the present invention are not particularly limited in terms of their sources, and are all conventional products that can be purchased through regular commercial channels, or can be prepared according to conventional methods well known to those skilled in the art. Example
[0046] Example 1
[0047] Nickel nitrate (2.91 g), cobalt nitrate (2.92 g), and sodium tungstate (3.30 g) were weighed and added into a beaker filled with deionized water (150 mL). The mixture was stirred magnetically for 30 min, and then transferred to a reactor. A piece of 0.5 cm × 1.5 cm carbon cloth (CC) was placed in the reactor. The reactor was sealed and allowed to react in an oven at 120 °C for 6 h.
[0048] After the reaction solution was cooled to room temperature, CC was taken out, washed with anhydrous ethanol and deionized water, and dried in an oven at 60° C. to obtain WCoNi-pre / CC.
[0049] Sodium borohydride (0.12 g) was weighed and added to a beaker containing deionized water (60 mL). Se powder (0.08 g) was added under continuous magnetic stirring. After uniform dispersion, ammonia water (10 mL) was added and stirring was continued until the solution turned wine red.
[0050] The solution was transferred to a reaction kettle, and the WCoNi-pre / CC prepared above was placed in the reaction kettle. After being sealed, the reaction was allowed to stand in an oven at 180°C for 6 hours.
[0051] Take out WCoNi-pre / CC, wash it with anhydrous ethanol and deionized water, dry it in a 60°C oven, place it in a tube furnace, heat it to 400°C at a rate of 2°C / min, and heat it at a constant temperature for 2h to obtain W,Co-NiSe2 / CC catalyst.
[0052] Example 2
[0053] Nickel nitrate (2.91 g), cobalt nitrate (4.36 g), and sodium tungstate (4.95 g) were weighed and added to a beaker filled with deionized water (150 mL). The mixture was stirred magnetically for 30 min, and then transferred to a reactor. A piece of 0.5 cm × 1.5 cm carbon cloth (CC) was placed in the reactor. The reactor was sealed and allowed to react in an oven at 130 °C for 5 h.
[0054] After the reaction solution was cooled to room temperature, CC was taken out, washed with anhydrous ethanol and deionized water, and dried in an oven at 60° C. to obtain WCoNi-pre / CC.
[0055] Sodium borohydride (0.10 g) was weighed and added to a beaker containing deionized water (60 mL). Se powder (0.09 g) was added under continuous magnetic stirring. After uniform dispersion, ammonia water (10 mL) was added and stirring was continued until the solution turned wine red.
[0056] The solution was transferred to a reactor, and the WCoNi-pre / CC prepared above was placed in the reactor. After being sealed, the reactor was placed in an oven at 170°C for reaction for 5 h.
[0057] Take out WCoNi-pre / CC, wash it with anhydrous ethanol and deionized water, dry it in a 60°C oven, place it in a tube furnace, heat it to 350°C at a rate of 2°C / min, and heat it at a constant temperature for 2h to obtain W,Co-NiSe2 / CC catalyst.
[0058] Example 3
[0059] Nickel nitrate (2.91 g), cobalt nitrate (5.84 g), and sodium tungstate (6.60 g) were weighed and added into a beaker filled with deionized water (150 mL). The mixture was stirred magnetically for 30 min, and then transferred to a reactor. A piece of 0.5 cm × 1.5 cm carbon cloth (CC) was placed in the reactor. The reactor was sealed and allowed to react in an oven at 140 °C for 7 h.
[0060] After the reaction solution was cooled to room temperature, CC was taken out, washed with anhydrous ethanol and deionized water, and dried in an oven at 60° C. to obtain WCoNi-pre / CC.
[0061] Sodium borohydride (0.14 g) was weighed and added to a beaker containing deionized water (60 mL). Se powder (0.10 g) was added under continuous magnetic stirring. After uniform dispersion, ammonia water (10 mL) was added and stirring was continued until the solution turned wine red.
[0062] The solution was transferred to a reaction kettle, and the WCoNi-pre / CC prepared above was placed in the reaction kettle. After being sealed, the reaction was allowed to stand in an oven at 190°C for 7 hours.
[0063] Take out WCoNi-pre / CC, wash it with anhydrous ethanol and deionized water, dry it in a 60℃ oven, place it in a tube furnace, heat it to 450℃ at a rate of 2℃ / min, and heat it at a constant temperature for 2h to obtain W,Co-NiSe2 / CC catalyst.
[0064] Comparative Example 1
[0065] Nickel nitrate (2.91 g) was weighed and added to a beaker containing deionized water (150 mL). The mixture was stirred magnetically for 30 min and transferred to a reactor. A piece of 0.5 cm × 1.5 cm carbon cloth (CC) was placed in the reactor. The reactor was sealed and allowed to react in an oven at 120 °C for 6 h.
[0066] After the reaction solution was cooled to room temperature, CC was taken out, washed with anhydrous ethanol and deionized water, and dried in an oven at 60° C. to obtain Ni-pre / CC.
[0067] Sodium borohydride (0.12 g) was weighed and added to a beaker containing deionized water (60 mL). Se powder (0.08 g) was added under continuous magnetic stirring. After uniform dispersion, ammonia water (10 mL) was added and stirring was continued until the solution turned wine red.
[0068] The solution was transferred to a reaction kettle, and the Ni-pre / CC prepared above was placed in the kettle. After sealing, the reaction was allowed to stand in an oven at 180°C for 6 hours.
[0069] The Ni-pre / CC was taken out, washed with anhydrous ethanol and deionized water, dried in an oven at 60°C, placed in a tube furnace, heated to 400°C at a rate of 2°C / min, and heated at a constant temperature for 2h to obtain a NiSe2 / CC catalyst.
[0070] Comparative Example 2
[0071] Nickel nitrate (2.91 g) and sodium tungstate (3.30 g) were weighed and added into a beaker containing deionized water (150 mL). The mixture was stirred magnetically for 30 min and transferred into a reactor. A piece of 0.5 cm × 1.5 cm carbon cloth (CC) was placed in the reactor. The reactor was sealed and allowed to react in an oven at 120 °C for 6 h.
[0072] After the reaction solution was cooled to room temperature, CC was taken out, washed with anhydrous ethanol and deionized water, and dried in an oven at 60° C. to obtain WNi-pre / CC.
[0073] Sodium borohydride (0.12 g) was weighed and added to a beaker containing deionized water (60 mL). Se powder (0.08 g) was added under continuous magnetic stirring. After uniform dispersion, ammonia water (10 mL) was added and stirring was continued until the solution turned wine red.
[0074] The solution was transferred to a reaction kettle, and the WNi-pre / CC prepared above was placed in the reaction kettle. After being sealed, the reaction was allowed to stand in an oven at 180°C for 6 hours.
[0075] Take out WNi-pre / CC, wash it with anhydrous ethanol and deionized water, dry it in a 60°C oven, place it in a tube furnace, heat it to 400°C at a rate of 2°C / min, and heat it at a constant temperature for 2h to obtain W-NiSe2 / CC catalyst.
[0076] Comparative Example 3
[0077] Nickel nitrate (2.91 g) and cobalt nitrate (2.92 g) were weighed and added to a beaker containing deionized water (150 mL). The mixture was stirred magnetically for 30 min and transferred to a reactor. A piece of 0.5 cm × 1.5 cm carbon cloth (CC) was placed in the reactor. The reactor was sealed and allowed to react in an oven at 120 °C for 6 h.
[0078] After the reaction solution was cooled to room temperature, CC was taken out, washed with anhydrous ethanol and deionized water, and dried in an oven at 60° C. to obtain CoNi-pre / CC.
[0079] Sodium borohydride (0.12 g) was weighed and added to a beaker containing deionized water (60 mL). Se powder (0.08 g) was added under continuous magnetic stirring. After uniform dispersion, ammonia water (10 mL) was added and stirring was continued until the solution turned wine red.
[0080] The solution was transferred to a reaction kettle, and the CoNi-pre / CC prepared above was placed in the reaction kettle. After sealing, the reaction was allowed to stand in an oven at 180°C for 6 hours.
[0081] The CoNi-pre / CC was taken out, washed with anhydrous ethanol and deionized water, dried in an oven at 60°C, placed in a tube furnace, heated to 400°C at a rate of 2°C / min, and heated at a constant temperature for 2h to obtain the Co-NiSe2 / CC catalyst.
[0082] Figure 1 The X-ray diffraction patterns of the catalysts prepared in Example 1 and Comparative Examples 1-3 are shown.
[0083] from Figure 1As can be seen in (a), NiSe2 diffraction peaks appeared in the prepared different catalysts. Among them, the diffraction peaks at 30.14°, 33.78°, 37.11°, 43.19°, 51.03°, 55.78°, and 58.07° correspond to the (200), (210), (211), (220), (311), (023), and (321) crystal planes of NiSe2 (PDF#88-1711), respectively. However, no diffraction peaks of W and Co were observed, indicating that after doping with W and Co, the crystal structure of NiSe2 did not change, and no other crystal phases were formed.
[0084] in addition, Figure 1 (b) is a local magnified XRD image, from which we can see that the (211) crystal plane position of NiSe2 has shifted significantly. This is due to the lattice distortion caused by the different intrinsic ion radii of W, Co, and Ni, and also proves the successful doping of W and Co.
[0085] Application Examples
[0086] The W, Co-NiSe2 / CC, NiSe2 / CC, W-NiSe2 / CC, and Co-NiSe2 / CC prepared in the above Example 1 and Comparative Examples 1 to 3 were directly used as working electrodes, a 3.0 cm × 4.0 cm stainless steel sheet was used as a counter electrode, and a mercury oxide electrode was used as a reference electrode. A three-electrode system was used to characterize the electrochemical properties of different catalysts by cyclic voltammetry (CV).
[0087] 1.0 M KOH and 1.0 M KOH + 0.33 M Urea solution were used as electrolyte solutions, respectively. Shanghai Chenhua CHI660E electrochemical workstation was used to measure the voltage at 50 mVs at -0.055 to 0.800 V. -1 The urea electrochemical oxidation (UOR) reaction activity was tested at a scan rate of .
[0088] Figure 2 All catalysts have obvious redox peaks. The peaks in the voltage range of 1.3 V to 1.6 V correspond to Ni 2+ / Ni 3+ Oxidation peak, the peak in the voltage range of 1.0V to 1.4V corresponds to Ni 2+ / Ni 3+ It can also be seen from the figure that among the four catalysts, W,Co-NiSe2 / CC has the largest peak area and the highest peak current density, indicating that NiOOH active species are more easily generated on the surface of W,Co-NiSe2 / CC catalyst, thus having the best catalytic activity for UOR.
[0089] Figure 3The UOR catalytic activity of the prepared different catalysts was tested in 1.0M KOH+0.33M urea electrolyte. Although the figure shows that all catalysts have catalytic performance for UOR, the catalytic performance is obviously different. At 1.724V (vs RHE), the current density of W,Co-NiSe2 / CC catalyst (363.24mA cm -2 ) is the highest and significantly higher than W-NiSe2 / CC (318.8 mA cm -2 )、Co-NiSe2 / CC(295.08mA cm -2 ) and NiSe2 / CC (271.68 mA cm -2 ).
[0090] In order to better compare the UOR catalytic activities of different catalysts, the catalysts were further investigated at 10 mA cm -2 The voltage corresponding to the current density is, Figure 4 It shows that W,Co-NiSe2 / CC reaches 10mA cm -2 The voltage required for the current density is only 1.298V, which is lower than Co-NiSe2 / CC (1.319V), W-NiSe2 / CC (1.367V) and NiSe2 / CC (1.376V). It can be seen that W doping is beneficial to the improvement of catalytic performance, and the lower voltage to achieve the same current density is attributed to Co doping, proving that bimetallic doping can effectively improve the UOR catalytic activity of the catalyst.
[0091] like Figure 5 As shown in the figure, after 100 h of CA test, the current density of W,Co-NiSe2 / CC catalyst increased from 111.4 mA cm -2 It dropped to 91 mA cm -2 The retention rate is 81.7%. In terms of stability, W,Co-NiSe2 / CC catalyst still maintains the best performance.
[0092] The above embodiments of the present invention do not describe all the details in detail, nor limit the present invention to the above embodiments. Various changes, modifications, substitutions and variations made by ordinary technicians in this field without departing from the principles and purpose of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing an alkaline system urea oxidation catalyst, comprising: S1: nickel salt, tungstate and cobalt salt are dissolved in water, carbon cloth is added, and a carbon cloth-supported catalyst precursor is prepared by hydrothermal reaction at 120-140°C; S2: placing the carbon cloth-supported catalyst precursor in a medium containing Se 2- In an aqueous solution, a selenization hydrothermal reaction is carried out at 170-190°C; S3 calcining the selenization hydrothermal reaction product at a high temperature of 350-450° C. in an inert environment to prepare a carbon cloth-supported tungsten- and cobalt-doped nickel-selenide-based composite catalyst W,Co-NiSe2 / CC.
2. The method for preparing the alkaline system urea oxidation catalyst according to claim 1, characterized in that The nickel salt is any one of nickel sulfate, nickel nitrate, nickel chloride or nickel acetate; the tungstate is any one of sodium tungstate, calcium tungstate or ammonium tungstate; the cobalt salt is any one of cobalt nitrate, cobalt chloride or cobalt sulfate.
3. The method for preparing the alkaline system urea oxidation catalyst according to claim 1, characterized in that The molar ratio of the nickel salt, tungstate and cobalt salt is 1:(1-2):(1-2).
4. The method for preparing the alkaline system urea oxidation catalyst according to claim 1, characterized in that The Se 2- The aqueous solution is obtained by reducing selenium powder with any one of hydrazine hydrate, sodium borohydride or lithium aluminum hydride as a reducing agent.
5. The method for preparing the alkaline system urea oxidation catalyst according to claim 4, characterized in that Sodium borohydride is used as a reducing agent to reduce selenium powder in an alkaline aqueous solution to obtain the Se-containing 2- of aqueous solution.
6. The method for preparing the alkaline system urea oxidation catalyst according to claim 5, characterized in that The molar amount of selenium powder is 1.1 to 1.3 times the molar amount of nickel salt.
7. The method for preparing the alkaline system urea oxidation catalyst according to claim 1, characterized in that The hydrothermal reaction time and the selenization hydrothermal reaction time are both 5 to 7 hours.
8. The method for preparing the alkaline system urea oxidation catalyst according to claim 1, characterized in that The high temperature calcination time is not less than 2 hours.
9. An alkaline system urea oxidation catalyst prepared by the preparation method of claim 1, wherein the catalyst has NiSe2 as an active component, is doped with W and Co bimetallics, and is directly loaded on a carbon cloth.
10. Use of the alkaline system urea oxidation catalyst according to claim 9 as an anode material for a urea fuel cell.
Citation Information
Cited By
Preparation and application of PILs / PPy / GO modified glassy carbon electrode
CN120490251A